ARRANGEMENT OF URBAN VILLAGE UTILITIES AND FACILITIES BASED ON COMMUNITY NEEDS IN KAMPUNG MUKA, ANCOL SUB DISTRICT, NORTH JAKARTA - Anita Sitawati Wartaman; Putri Ayu Parahyangan; Anindita Ramadhani (Universitas Trisakti, 2023)
In 2018 The Governor of DKI Jakarta established a regulation to rearrange some settlements in order to improve the resident’s quality of life. Based on DKI Jakarta Governor’s Decree Number 878 of 2018 there are 21 villages that would be arranged, one of which is Kampong Muka in North Jakarta. Kampung Muka has the character of an urban village, namely, a large population with a heterogeneous nature and its location is close to the economic center. Kampung Muka has minimal open space, limited land, and narrow street corridors, impacting on the lack of facilities and infrastructure in the area. To compose an effective arrangement, it is necessary to understand the needs of the community residents. This study aims to identify kampong arrangements of infrastructures and facilities based on regulation and community perception. The method uses Indonesian Minimum Standard of residential environment to gauge the adequacy of facilities and utilities of the kampong. Then, a Likert scale to score the community’s perception toward the needs of kampong arrangement. Theresult showed that there are five unmet facilities, namely kindergarten facilities, elementary school facilities, meeting halls, worship places and parks; and one infrastructure that has not been met, namely telephone network. However, based on the community’s perception, the residents only need one facility, namely meeting hall. By the results, it is necessary to understand the needs of the people instead of referring on standard and regulation only. Therefore, the arrangement for Kampung Muka is prioritized to provide meeting hall for the residents